Proceedings of SPE Annual Technical Conference and Exhibition 2007
DOI: 10.2523/109965-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low-Salinity Waterflooding to Improve Oil Recovery-Historical Field Evidence

Abstract: Waterflooding is by far the most widely applied method of improved oil recovery. Crude oil/water/rock interactions can lead to large variations in the displacement efficiency of waterfloods. Laboratory waterflood tests and single-well tracer tests in the field have shown that injection of low-salinity water can increase oil recovery, but work designed to test the method on a multi-well field scale has not yet been undertaken. Historical waterflood records could unintentionally provide some evidence of improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…It was found that water chemistry has a significant impact on recovery factor (Morrow and Buckley 2011). Several field trials proved the efficiency of low salinity water in improving oil recovery (Webb et al 2004;Robertson et al 2007;Lager et al 2008). In addition, several experimental work showed the success of low salinity water in both secondary and tertiary recovery mode (Zhang et al 2007;Agbalaka et al 2009), but sometimes for only one or the other (Zhang and Morrow 2006).…”
Section: Introductionmentioning
confidence: 95%
“…It was found that water chemistry has a significant impact on recovery factor (Morrow and Buckley 2011). Several field trials proved the efficiency of low salinity water in improving oil recovery (Webb et al 2004;Robertson et al 2007;Lager et al 2008). In addition, several experimental work showed the success of low salinity water in both secondary and tertiary recovery mode (Zhang et al 2007;Agbalaka et al 2009), but sometimes for only one or the other (Zhang and Morrow 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, from a large dataset of waterflooding in Wyoming fields available in public records, Thyne, et al [191] published a comprehensive evaluation of historical low saline brine injection in 26 fields and compared with laboratory corefloods. In contrast to Robertson [190], they found no correlation between dilution and oil recovery. It was concluded based on historical field and coreflood data that no benefit was associated with low saline brine injection.…”
Section: Sandstone Reservoirsmentioning
confidence: 64%
“…Elsewhere, in the Powder River basin of Wyoming, Robertson [190] published the comparison of three Minnelusa field performances based on historical evidence of unintentional injection of low saline brine. It was reported that the oil recovery trend in historical data appeared to increase as the salinity ratios decreased, which corrobated laboratory corefloods using Berea outcrop material.…”
Section: Sandstone Reservoirsmentioning
confidence: 99%
“…Numerous sandstone fields were waterflooded using low salinity formation brine (1,000 ppm) (Robertson et al 2003;Robertson 2007). Crude oil and rock types, particularly the presence and distribution of kaolinite, both play a dominant role in the effect that brine composition has on waterflood oil recovery.…”
Section: Literature Reviewmentioning
confidence: 99%